2015
DOI: 10.1063/1.4928741
|View full text |Cite
|
Sign up to set email alerts
|

A new approach to the problem of bulk-mediated surface diffusion

Abstract: This paper is devoted to bulk-mediated surface diffusion of a particle which can diffuse both on a flat surface and in the bulk layer above the surface. It is assumed that the particle is on the surface initially (at t = 0) and at time t, while in between it may escape from the surface and come back any number of times. We propose a new approach to the problem, which reduces its solution to that of a two-state problem of the particle transitions between the surface and the bulk layer, focusing on the cumulativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 36 publications
3
26
1
Order By: Relevance
“…This paper extends the formalism developed for unbiased bulk-mediated surface diffusion in Ref. 35 to the case where the particle has arbitrary drift velocities on the surface and in the bulk. This is done in Secs.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…This paper extends the formalism developed for unbiased bulk-mediated surface diffusion in Ref. 35 to the case where the particle has arbitrary drift velocities on the surface and in the bulk. This is done in Secs.…”
Section: Discussionmentioning
confidence: 83%
“…Recently we proposed an alternative approach to this problem 35 that focuses on the cumulative time spent by the particle on the surface. The approach exploits the fact that the free-particle propagators on the surface and in the bulk are Gaussian.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, one can consider the effect of local potentials near the boundary (such as, e.g., electrostatic repulsion or attractive interactions) onto the statistics of boundary encounters. To some extent, such an approach can provide a microscopic model for so-called intermittent diffusions, in which a particle alternates diffusions in the bulk and on the surface [59][60][61][62][63][64][65][66][67][68]. One can also consider other surface reaction mechanisms [8] and investigate how the drift may affect them.…”
Section: Discussionmentioning
confidence: 99%
“…Berezhkovskii et al . [ 16 ] found that bulk-mediated diffusion was most significant at a specific bulk layer thickness.…”
Section: Methodsmentioning
confidence: 99%